Ochre provenance and procurement strategies during the middle stone age at Diepkloof Rock Shelter, South Africa - (:unkn) unknown (My University, 2016)
Usually referred to in archaeological contexts simply as ‘ochre’, ferruginous rocks were commonly used during the Middle Stone Age (MSA) in South Africa. While ochre use by early modern humans has often been interpreted as reflecting complex behaviours, related procurement strategies and selection criteria remain poorly documented. Eight ochre sources from the surroundings of Diepkloof rock shelter in South Africa and 28 ochre pieces from the site's MSA levels were studied by XRD, ICP–OES and ICP–MS. Mineralogical and geochemical data demonstrate that ochre was both locally procured and transported to the site from more distant sources. Here, we investigate the reasons underlying the choice of particular local and non‐local ochre sources exploited at Diepkloof, emphasizing differences in their physico‐chemical properties. Regardless of the motivations behind ochre selection, our data shed new light on the behavioural complexity of MSA societies and suggest that ochre procurement strategies may be independent of subsistence concerns.
Keywords: African Research